Manajemen Peserta Didik dalam Program Sistem Kredit Semester (SKS) untuk Meningkatkan Nilai Akademis di MTsN 2 Medan - Marpaung, Wardatun Thaibah; Siahaan, Amiruddin (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to describe student management within the Semester Credit System (SKS) program as a strategy to enhance the quality of education, particularly in the academic aspect, at MTsN 2 Medan. The SKS program is designed to provide educational services tailored to each student's interests, talents, abilities, and learning pace. This research employs a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation. The findings reveal that the implementation of student management in the SKS program at MTsN 2 Medan involves several stages: planning, organizing, implementation, supervision, and evaluation. These stages actively involve the principal, vice principal, program coordinator, teachers, and students. The program has been proven to improve students' academic performance. Its success is largely influenced by the effective and efficient application of student management practices. Therefore, the SKS program serves as a strategic alternative for improving the quality of education and achieving academic goals. The results of this study contribute significantly to the field of education and can serve as a reference for policy development and educational practice aimed at enhancing the quality and academic achievement of students.